Robustness of sweeping-window arc therapy treatment sequences against intrafractional tumor motion - Fleckenstein, Jens; Hesser, Jürgen; Wenz, Frederik; Lohr, Frank (Medical physics, 2015)
Purpose: Due to the potentially periodic collimator dynamic in volumetric modulated arc therapy (VMAT) dose deliveries with the sweeping-window arc therapy (SWAT) technique, additional manifestations of dosimetric deviations in the presence of intrafractional motion may occur. With a fast multileaf collimator (MLC), and a flattening filter free dose delivery, treatment times close to 60 s per fraction are clinical reality. For these treatment sequences, the human breathing period can be close to the collimator sweeping period. Compared to a random arrangement of the segments, this will cause a further degradation of the dose homogeneity. Methods: Fifty VMAT sequences of potentially moving target volumes were delivered on a two dimensional ionization chamber array. In order to detect interplay effects along all three coordinate axes, time resolved measurements were performed twice—with the detector aligned in vertical (V) or horizontal (H) orientation. All dose matrices were then moved within a simulation software by a time-dependent motion vector. The minimum relative equivalent uniform dose EUDr,m for all breathing starting phases was determined for each amplitude and period. Furthermore, an estimation of periods with minimum EUD was performed. Additionally, LINAC logfiles were recorded during plan delivery. The MLC, jaw, gantry angle, and monitor unit settings were continuously saved and used to calculate the correlation coefficient between the target motion and the dose weighed collimator motion component for each direction (CC, LR, AP) separately. Results: The resulting EUDr,m were EUDr,m(CCV) = (98.3 ± 0.6)%, EUDr,m(CCH) = (98.6 ± 0.5)%, EUDr,m(APV) = (97.7 ± 0.9)%, and EUDr,m(LRH) = (97.8 ± 0.9)%. The overall minimum relative EUD observed for 360∘ arc midventilation treatments was 94.6%. The treatment plan with the shortest period and a minimum relative EUD of less than 97% was found at T = 6.1 s. For a partial 120∘ arc, an EUDr,m = 92.0% was found. In all cases, a correlation coefficient above 0.5 corresponded to a minimum in EUD. Conclusions: With the advent of fast VMAT delivery techniques, nonrobust treatment sequences for human breathing patterns can be generated. These sequences are characterized by a large correlation coefficient between a target motion component and the corresponding collimator dynamic. By iteratively decreasing the maximum allowed dose rate, a low correlation coefficient and consequentially a robust treatment sequence are ensured.